COPB2: A Novel Prognostic Biomarker That Affects Progression of HCC. (22nd March 2021) - Zhang, Jiayao; Wang, Xiaoyu; Li, Guangbing; He, Jingyi; Lu, Ziwen; Yang, Yang; Jiang, Yong; Jiang, Liyong; Li, Feiyu; Liu, Jun
Abstract : Purpose . This study is aimed at investigating the expression, underlying biological function, and clinical significance of coatomer protein complex subunit beta 2 (COPB2) in hepatocellular carcinoma (HCC). Methods . HCC-related data were extracted from The Cancer Genome Atlas (TCGA) database, International Cancer Genome Consortium (ICGC) database, and Gene Expression Omnibus (GEO) database. A logistic regression module was applied to analyze the relationship between the expression of COPB2 and clinicopathologic characteristics. The Cox proportional hazard regression model and Kaplan–Meier method were used for survival analysis. Gene set enrichment analysis (GSEA) was used to annotate the underlying biological functions. Loss-of-function experiments were conducted to determine the underlying mechanisms. Results . COPB2 was overexpressed in HCC, and high expression of COPB2 was significantly correlated with higher alpha fetoprotein (AFP) (odds ratio OR = 1.616, >20 vs. ≤20, p < 0.05 ), stage (OR = 1.744, III vs. I, p < 0.05 ), and grade (OR = 1.746, G4+G3 vs. G2+G1, p < 0.05 ). Kaplan–Meier survival analysis showed that HCC patients with high COPB2 expression had a worse prognosis than those with low COPB2 expression (p < 0.0001 for TCGA cohort, p < 0.05 for ICGC cohort). The univariate Cox (hazard ratio HR = 1.068, p < 0.0001 ) and multivariate Cox (HR = 2.011, p < 0.05 ) regression analyses suggested that COPB2 was an independent risk factor. GSEA showed that mTOR and other tumor-related signaling pathways were differentially enriched in the high COPB2 expression phenotype. Silencing of COPB2 inhibited the proliferation, migration, and invasion abilities by suppressing epithelial-mesenchymal transition and mTOR signaling. Conclusion . COPB2 is a novel prognostic biomarker and a promising therapeutic target for HCC.